New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from Colombia, Ecuador and Peru - Ale-Rocha, R. (Zootaxa, 2007)
Eleven new species of Neohybos Ale-Rocha & Carvalho are described from Colombia, Ecuador and Peru: N. bicolor (Ecuador); N. brunnescens (Colombia); N. colombiensis (Colombia); N. cooperi (Colombia); N. cupreus (Ecuador); N. elegans (Ecuador, Colombia); N. fuscipes (Ecuador); N. longiventris (Peru), N. schlingeri (Colombia), N. rossi (Colombia) and N. tenuis (Ecuador, Colombia).